A new species of Neopronematus and a re-description of Pronematus rykei Meyer & Rodrigues (Acari: Iolinidae) from Iran - Ahmad-Hosseini, Mohammad; Khanjani, Mohammad; Karamian, Roya (Zootaxa, 2017)
Neopronematus iranensis sp. nov. is described and illustrated and the female and male of Pronematus rykei (Meyer & Rodrigues, 1966) are re-described and reported for the first time from Iran. These species were collected from walnut leaves infested by leaf blister mite, Aceria tristriatus, (Nalepa, 1890), in Hamedan and Lorestan provinces, Iran. Furthermore, a key to all known species of Neopronematus is provided.